1995
DOI: 10.1017/s1037291100001679
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of guidance officer selection criteria

Abstract: Unresponsive design guidelines for open spaces and the continuous allocation of land for the construction of buildings has led to the 'concretisation' of urbanscapes. This has resulted in the urban heat island effect marking the increase in air temperature making urban spaces almost unbearable for urban residents to dwell in. However, new effort is being made to reduce the effect of heat gain at the pedestrian level by planting vegetation in open spaces particularly urban nodes to create a comfortable outdoor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Some early criticisms include that school psychologists/guidance officers should be more involved in the classroom (Carpenter, 1979), should be less isolated from school business and should have better documented roles and responsibilities for which they can be held accountable (Valine, Higgins, & Harcher, 1982). Communication skills are critical (Beavers, 1995), and according to data presented by Dickinson (1995), the communication and consultation skills of school psychologists/guidance officers are not always perceived to be adequate. Unfortunately, all of this critical discourse has yet to lead to any clear consensus on the role or function of a group attempting to balance the science and practice of their profession (Partin, 1993).…”
mentioning
confidence: 99%
“…Some early criticisms include that school psychologists/guidance officers should be more involved in the classroom (Carpenter, 1979), should be less isolated from school business and should have better documented roles and responsibilities for which they can be held accountable (Valine, Higgins, & Harcher, 1982). Communication skills are critical (Beavers, 1995), and according to data presented by Dickinson (1995), the communication and consultation skills of school psychologists/guidance officers are not always perceived to be adequate. Unfortunately, all of this critical discourse has yet to lead to any clear consensus on the role or function of a group attempting to balance the science and practice of their profession (Partin, 1993).…”
mentioning
confidence: 99%
“…While it may be surprising that traditional tasks such as assessment, program planning, and counselling did not feature on this list, Dickinson concluded that the key area affecting guidance roles in secondary schools was consultation and communication between guidance officers and school principals. In the light of this finding it is interesting to note that Beavers (1995), in a study into guidance officer selection criteria, also identified communication skill training as "critically important . .…”
Section: Don Rice and Paul Bramstonmentioning
confidence: 99%